Peningkatan Kapasitas UMKM Kreatif melalui Pelatihan Pembuatan Souvenir Khas Wisata Yamansari, Kabupaten Tegal - Yoga Prihatin,; Nadya Shafira Salsabilla,; Nur Tulus Ujianto,; Bagus Fahmi Maarif,; Sandi Yudha Pradana, (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Creative micro, small, and medium enterprises (MSMEs) play an important role in supporting local economic development, particularly in tourism areas. Yamansari Village, Tegal Regency, has tourism potential that can be developed through distinctive local souvenir products. However, local MSMEs face several challenges, including limited production skills, lack of design innovation, and insufficient understanding of product quality and marketing. This community service program aims to enhance the capacity of creative MSMEs through training in the production of Yamansari tourism souvenirs with economic value and competitiveness. The implementation method includes identifying MSME needs, preparing training materials, conducting participatory training sessions, and providing mentoring and evaluation. The training focuses on improving technical skills in souvenir production, developing design creativity based on local wisdom, and introducing basic packaging and marketing strategies. The results show an increase in participants’ knowledge, skills, and motivation to produce more diverse and attractive souvenir products. The implications of this program include opportunities to increase MSME income and strengthen the tourism identity of Yamansari Village through the sustainable development of distinctive souvenir products.